Competences and Barriers for the Evidence-Based Practice in Nursing: an integrative review - Camargo,Fernanda Carolina (2018)
ABSTRACT Objective: To analyze knowledge, attitudes, practices, and frequent barriers to the implementation of the Evidence-Based Practice among nursing assistants in the hospital. Method: This is an integrative review, whose search for primary studies occurred in the PubMed, CINAHL and LILACS databases. For the analysis, cross-sectional observational studies were included in English, Portuguese and Spanish, published in nursing journals, from January 2007 to July 2016. Results: The search resulted in 363 articles, including nine primary studies. The sources of recurrent evidence among care nurses were: personal experience and local care protocols. These professionals presented weaknesses in the implementation of the Evidence-Based Practice related to the lack of knowledge for evidence evaluation, work overload and resistance to change of practice. Final considerations Nurses presented favorable attitudes, however, with little knowledge to perform the Evidence-Based Practice. Results can support interventions for its implementation in the hospital.